P1405ETELCALCETIDE USE IN HEMODIALYTIC PATIENTS: A SINGLE CENTER EXPERIENCE. (6th June 2020) - Covella, Bianca; Rossi, Luigi; Libutti, Pasquale; Corciulo, Simone; Manno, Elisabetta; Lomonte, Carlo
Abstract: Background and Aims: Etelcalcetide is an injectable calcimimetic, utilized to treat secondary hyperparathyroidism. Recently introduced as alternative to cinacalcet, it acts on a different CaSR (Calcium Sensor Receptor) binding site. Outlined advantages are the intravenous formulation, which solves non adherence, the lower gastrointestinal side effects incidence. The main limitation is iatrogenic hypocalcemia. We show our experience to evaluate findings of our initial fieldwork in order to optimize drug efficacy, safety and tolerability Method: We included 27 patients during 2018 (15 M and 12 F, Caucasian, mean age 60, 7±13, 7 years), followed for at least 6 months. Initial etelcalcetide dose was 15 mg in all patients. PTH, Calcium, Phosphorus monitoring was done every month. Concomitant drugs as phosphorus binders, Vitamin D or analogues, Calcium and the switch from cinacalcet were considered. Therapeutic variations and side effects were recorded. Data are registered at the beginning and the end of follow up. Results: Starting values are: PTH 1298±545 pg/ml, Calcium 9, 1±0, 9, Phosphorus 5, 1±1, 4. 14 patients already took phosphorus binders, 10 paricalcitol. 12 patients were switched from Cinacalcet because of non-adherence or inefficacy, the other 15 patients never took calcimimetics. Mean values after 6 months are: PTH 661±469 pg/ml, Calcium 8, 2±0, 5 mg/ml, Phosphorus 4, 1±1, 6 mg/ml. These data point out a mean decrease in PTH value of 49%, reaching the therapeutic target in 18 patients, that is the 75% of the total population studied. It have been necessary dose modifications in 15 patients (62.5%): 9 etelcalcetide dose variations (37, 5%), 6 vitamin D and Calcium supplementation, both the changes in 5 of them. Side effects were hypocalcemia (14), pruritus (1), diarrhea (1), low platelet count (1), registered in 17 patients (63%), 3 of them withdrew therapy and then refused to start it again. It has to be said that thrombocytopenia, occurred after the follow up time (at 7 th month), solve after etelcacetide withdrawal. Subgroup analysis pointed out a statistically significant correlation between drug efficacy and switch from cinacalcet, both in terms of extent of iPTH reduction (65% vs 42% - p value < 0, 05 ) and of achievement of the therapeutic target ( 89% vs 66% - p value < 0, 05), and between concomitant paricalcitol therapy at zero-time and lower hypocalcemia incidence (10% vs 76% - p value < 0, 05). Conclusion: Results confirm etelcalcetide efficacy and suggest a correlation between concomitant paricalcitol therapy at baseline and lower hypocalcemia incidence and between greater efficacy and switch from cinacalcet. These data, if confirmed in larger sample, could be useful to guide the starting approach and the maintaining treatment with etelecalcetide.